1993
DOI: 10.1002/ccd.1810290216
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal sealing of vascular wall disruptions with radiofrequency‐heated balloon angioplasty

Abstract: Suboptimal luminal widening or acute closure secondary to arterial dissection remain significant risks of percutaneous transluminal balloon angioplasty. Non surgical techniques are often employed in an attempt to repair dissections either as temporary or definitive treatment. The aim of this study was to test the hypothesis that radiofrequency thermal balloon angioplasty at an operating temperature of 70 degrees C and low inflation pressure could seal dissections and perforations in a model of severe arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The latter is also shown in the threedimensional images of confocal microscopy. These findings are in agreement with previous studies that have shown thermal injury of RF treated arteries, including transmural coagulation necrosis, flattening of the internal elastic lamina, and medial thinning [19,20]. The effect of thermal energy on the depth of medial necrosis and extent of arterial wall thinning is temperature-dependent as demonstrated by histologic studies [10].…”
supporting
confidence: 90%
“…The latter is also shown in the threedimensional images of confocal microscopy. These findings are in agreement with previous studies that have shown thermal injury of RF treated arteries, including transmural coagulation necrosis, flattening of the internal elastic lamina, and medial thinning [19,20]. The effect of thermal energy on the depth of medial necrosis and extent of arterial wall thinning is temperature-dependent as demonstrated by histologic studies [10].…”
supporting
confidence: 90%